The devil came on horseback [videorecording (DVD)] - Stern, Ricki; Sundberg, Annie; Steidle, Brian (Docurama : Distributed by New Video Group, 2007)
This powerful and original film exposes the tragedy taking place in Darfur as seen through the eyes of an American witness, former U.S. Marine Captain Brian Steidle, who has since returned to the U.S. to take action to stop it.